The Experience Economy as the Future for European Agriculture and Food? - Johan Swinnen; Kristine Van Herck; Thijs Vandemoortele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
As recently as a century ago, one out of two people in Europe was employed in the agricultural sector. Today agriculture represents only a small fraction of total employment in most EU member states. What makes this decline in agricultural employment even more striking is that this evolution has occurred despite substantial EU subsidies to support firmers' income. Given the apparent ineffectiveness of government support in keeping agricultural employment steady, it is worth considering which firming activities are likely to be successful in the economy of the 21st century. We argue in this paper that a potential growth path for European agriculture is the ?experience economy? in which consumers are willing to pay premium prices for products and services that provide additional intangible ?experiences?. We discuss the growth potential of the ?experience economy? in the agricultural sector and conclude that it is worthwhile to consider the experience economy as a pathway for future firm growth.
Keywords: 330